Chemical profile and antihyperlipidemic effect of Portulaca oleracea L. seeds in streptozotocin-induced diabetic rats. Issue 12 (18th June 2018) - Nazeam, Jilan A.; El-Hefnawy, Hala M.; Omran, Gamal; Singab, Abdel-Naser
Abstract: Hypolipidemic effect of Portulaca oleracea L. seed extract and its fractions have been studied on streptozotocin (STZ) at dose 75 mg/kg b.wt. After fractionation of the alcoholic extract; petroleum ether fraction was the most active fraction that decreased different hyperlipidemia biochemical parameters. After chromatographic analysis; oleamide, ethylpalmitate, β -amyrin, stigmasterol and β -sitosterol were identified. The GLC analysis of unsaponifiable matter revealed the presence of; lignoceric acid as a major constituent in the most bioactive fraction. In conclusion, petroleum ether fraction possessed a hypolipidemic effect in STZ-induced diabetic rats, which may be attributed to its phytosterols, fatty acid and amide compounds. The finding of the present investigation strongly demonstrates the potential of non-polar fraction of P. oleracea L. seed in combating hyperlipidemia in diabetic condition. So the petroleum ether fractions and its constituents can be used as hypolipdemic supplement in the developing countries towards the development of new therapeutic agents. Abstract :